Pengaruh Senam Otak terhadap Ingatan Jangka Pendek pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Ni Made Kharisma Praba Yuanika; Saktivi Harkitasari; Ni Putu Sukarini; Komang Trisna Sumadewi; Tjok Istri Putra Parwati (Aesculapius Medical Journal, 2023)
[The Effect of Brain Gymnastics on Short-Term Memory in Students of the Faculty of Medical and Health Sciences, University of Warmadewa] Cognitive function is a complex function in the human brain that involves both short-term and long-term memory. Short-term memory upholds various aspects of life, for instance, academic achievement, so it needs to be trained. Short-term memory can be trained by doing brain exercises. It can optimize brain function. Brain exercise is a sequence of simple movements that can improve short-term memory. This is an experimental study that uses a quasi- experimental method with a pre-test and post-test control group design. The aim of this study is to determine the effect of brain exercises on students' short-term memory at the Faculty of Medical and Health Sciences, University of Warmadewa. This study uses students of the Faculty of Medical and Health Sciences, University of Warmadewa, class of 2021, as the sample. Purposive sampling is used as a sampling technique. The result of the statistical analysis shows a significant increase in the short-term memory of the experimental group that was given brain exercises 4 times a week for 2 weeks in both subtenses digit forward (p = 0.001) and digit backward (p = 0.002). On the other hand, in the control group who were not given brain exercise training, there was no increase in short-term memory in the digit forward (p = 0.162) and digit backward (p = 0.257) subtests. This study demonstrates that there is a positive effect of giving brain exercises on short-term memory in students of the Faculty of Medical and Health Sciences, University of Warmadewa.